Oggie Cooder - Weeks, Sarah (New York : Scholastic Press, 2008)
Quirky fourth-grader Oggie Cooder goes from being shunned to everyone's best friend when his uncanny ability to chew slices of cheese into the shapes of states wins him a slot on a popular television talent show, but he soon learns the perils of being a celebrity--and having a neighbor girl as his manager.
Keywords: Eccentrics and eccentricities -- Juvenile fiction; Celebrities -- Juvenile fiction; Ability -- Juvenile fiction; Self-esteem -- Juvenile fiction; Friendship -- Juvenile fiction; Schools -- Juvenile fiction